2023
DOI: 10.24294/jipd.v7i3.2583
|View full text |Cite
|
Sign up to set email alerts
|

Impact of big data analytics in project success: Mediating role of intellectual capital and knowledge sharing

Diego Norena-Chavez,
Eleftherios Thalassinos

Abstract: Purpose: This study empirically investigates the effect of big data analytics (BDA) on project success (PS). Additionally, in this study, the investigation includes an examination of how intellectual capital (IC) and (KS) act as mediators in the correlation between BDA and KS. Lastly, a connection between entrepreneurial leadership (EL) and BDA is also explored. Design/Methodology- Using a sample of 422 senior-level employees from the IT sector in Peru. The partial least squares structural equation modeling te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 104 publications
0
1
0
Order By: Relevance
“…Thus, governments should explore private sector financing as a means of involving private entities in infrastructure and public initiatives (Tavakolan and Nikoukar, 2022) while avoiding permanent ownership of infrastructure projects (Chen et al, 2022). In developing countries, financial crises and institutional inefficiencies exacerbate the challenge of allocating sufficient capital for the implementation of large projects (Tinsley, 2022;Norena-Chavez and Thalassinos, 2023).…”
Section: Project Financing Methodsmentioning
confidence: 99%
“…Thus, governments should explore private sector financing as a means of involving private entities in infrastructure and public initiatives (Tavakolan and Nikoukar, 2022) while avoiding permanent ownership of infrastructure projects (Chen et al, 2022). In developing countries, financial crises and institutional inefficiencies exacerbate the challenge of allocating sufficient capital for the implementation of large projects (Tinsley, 2022;Norena-Chavez and Thalassinos, 2023).…”
Section: Project Financing Methodsmentioning
confidence: 99%
“…The use and evolution of digital technologies and media have transformed customer interactions, but their journeys vary significantly worldwide (Nam et al, 2020;Kadlubek et al, 2022;Grima et al, 2023;Norena-Chavez and Thalassinos, 2023). Wan et al (2023) found that generic product recommendations boost early conversion rates, while retargeted ones increase late purchase funnel sales.…”
Section: Introductionmentioning
confidence: 99%